New techniques for an old disease: Sarcoptic mange in the Iberian wolf - Oleaga, Álvaro; Casais, Rosa; Balseiro, Ana; Gortázar, Christian (Veterinary Parasitology, 2011)
Sarcoptic mange, a parasitic skin infection caused by the burrowing mite Sarcoptes scabiei, has been reported in over 100 mammals, including humans. In endangered species, mange causes conservation concerns because it may decimate isolated populations and contribute to extinction. The Iberian Peninsula still maintains one of the largest wolf (Canis lupus) populations in Europe. In Iberia, sarcoptic mange is endemic in red foxes (Vulpes vulpes) and the first confirmed wolf mange cases were recently reported. However, knowledge on S. scabiei in wolves is scarce because of the sampling difficulties inherent to research on scarce species. In order to describe wolf mange epidemiology and to infer conservation implications, this study combined traditional laboratory techniques with the revision of wolf carcass pictures taken by field biologists and original information obtained by camera trapping. A total of 125 necropsies and 8783 camera-trap days allowed insights into wolf mange epidemiology between 2003 and 2010. Living Sarcoptes mites were detected in 19% of the fresh carcasses. Alopecic (delayed) type IV hypersensitive response reactions were observed, while parakeratotic lesions were infrequent. The number of mites isolated per wolf ranged from 1 to 78, and had a negative correlation with the percentage of alopecic skin. No effect by sex on mange prevalence was found. Yearlings showed a lower probability to present mange-compatible lesions than pups or adults. Wolves with mange-compatible lesions had a lower kidney fat index than apparently healthy ones. ELISA testing of 88 sera yielded an antibody prevalence of 20%. Photo-trapping recorded mange-compatible lesions since 2003 with a peak in 2008. The percentage of wolves with mange-compatible lesions registered in camera-traps during 1 year correlated with the percentage of red foxes with lesions in the previous year. This is the first large survey on sarcoptic mange in the Iberian wolf. Necropsy data, with alopecia as the main feature and a slight effect on ...